2020
DOI: 10.1370/afm.2469
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Delivered Cognitive Behavioral Training to Improve Functioning in Patients With Diabetes: A Cluster-Randomized Trial

Abstract: PURPOSE Cognitive behavioral therapy (CBT)-based programs delivered by trained community members could improve functioning and pain in individuals who lack access to such programs. We tested the effectiveness of a peer-delivered diabetes self-management program integrating CBT principles in improving physical activity, functional status, pain, quality of life (QOL), and health outcomes in individuals with diabetes and chronic pain. METHODSIn this community-based, cluster-randomized controlled trial, interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…We evaluated the effect of the CBT‐based peer support “Living Healthy” intervention on pain‐related outcomes among adults with diabetes and chronic pain, one of the first efforts combining CBT and peer support for chronic pain management. The intervention did not lead to change in A1c or BMI at 3‐month follow‐up, 29 but it did produce greater improvement in pain‐related self‐efficacy, pain intensity, and functioning, compared to the general health education group. Importantly, these results were sustained at 12‐month follow‐up after the intervention completion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We evaluated the effect of the CBT‐based peer support “Living Healthy” intervention on pain‐related outcomes among adults with diabetes and chronic pain, one of the first efforts combining CBT and peer support for chronic pain management. The intervention did not lead to change in A1c or BMI at 3‐month follow‐up, 29 but it did produce greater improvement in pain‐related self‐efficacy, pain intensity, and functioning, compared to the general health education group. Importantly, these results were sustained at 12‐month follow‐up after the intervention completion.…”
Section: Discussionmentioning
confidence: 76%
“…Peer advisors and participants were not blinded to the arm assignment for practical reasons. The primary trial outcomes included health‐related quality of life, functional status, glycated hemoglobin (A1c), systolic blood pressure (SBP), and body mass index 29 . The study was designed to provide 80% power to detect clinically important differences in A1c (0.4%) and SBP (4 mm Hg).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, in marginalised communities, it has been shown to foster wide benefits to civil society, economic and political engagement, and social development. 11-14…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this programme supports current studies that found lay people who have the skills to support diabetes patients, can improve self management behaviours, such as glucose levels, diet and exercise. 13-14 Thus, reducing complications and adverse outcomes for people with chronic conditions…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation